Factori simulativi/ blocanţi ai inovaţiei sociale în mediul rural românesc. Studiu de caz: comuna Bughea de Sus, jud. Argeş - Preotesi, Mihnea (Calitatea Vieții, 2009)
This study intends to make an analysis of how certain local contexts and particular ways of delivery welfare act upon the development of some of the premises which facilitate the social inovation. The analysis will be focused on the Romanian rural area. The groundwork hypothesis states that this represents a rather detrimental space to social inovation, and, in certain cases, a space favorable to the development of a particular type of social inovation entitled „pseudo-social innovation”. The suggested case study analyses a situation which I consider to be relevant, in order to describe how a combination of contextual variables represents detrimental premises for social innovation, facilitating the „pseudo-social innovation” behaviour.